The Role of Islamic Journalistics in the Implementation of Community Activities Restrictions (PPKM) Covid-19 - M. Yoserizal Saragih; Javaid Ahmad Andrabi (Budapest International Research and Critics University, 2021)
This article reviews the role of Islamic journalism in the midst of the Covid-19 PPKM, which is being highly discussed. The purpose of this article is so that the public can understand what is going on in the midst of the current PPKM Covid-19 polemic. This paper is a descriptive analysis which aims to describe, take an inventory, and analyze the conditions being investigated in a systematic, factual and accurate manner, then a conclusion is drawn from the results of the analysis. The results of the discussion analysis show that journalism not only records, conveys and disseminates information, but journalism also has an important role to the public as the leading guard in the midst of PPKM Covid-19. As for the role of Islamic journalism in the midst of the Covid-19 PPKM, namely as educators (muaddib), information straighteners (musaddid), reformers (mujaddid), unifiers (muwahid), and fighters (mujahid). In addition, Islamic journalism is also known as social control. In carrying out this role, Islamic jurisprudence also applies the principles of qaulan sadida (true words), qaulan baligha (effective words), qaulan ma'rufa (good words), qaulan karima (noble words), qaulan layina (gentle), qaulan maisura (easy to understand) with characteristics possessed by the Prophet such as shidiq (truth), amanah (trusted), tabligh (deliver), and fathonah (intelligent).